Socio-spatial practices in socio-technological peripheries: the introduction of the internet in rurban communities in Brazil and the United Kingdom - Lorena Melgaço Silva Marques (2016)
Despite the rapid incorporation of information and communication technologies (ICTs) in the everyday of rurban communities (those where urban and rural elements mingle), especially in the last decade, there is still a clear urban/non-urban gap regarding ICT access across the world, suggesting the existence and emergence of both exogenous and endogenous socio-technological peripheries. This can be understood as a global process present not only in the Global South/Eastperceived as peripheral, but also in the Global North/Westregarded as advanced and the motor of technological development. Locally, socio-technological peripheralisation accords with existing socio-spatial practices and with the ways ICTs are being introduced in the everyday. The interaction of socio-spatial practices and the internet, in turn, is part of an iterative process, that leads to further particularisations in the socio-spatial and socio-technological realms both in the Global North and South. This research focused on understanding the recursive interaction between socio-spatial practices and the late introduction of the internet in marginalised rurban communities. Its main premise was that there is an imbricated relationship between the socio-spatial organisation of the communities and the way people appropriate different sorts of socio-technical ensembles, in special, the internet. It also searched for indications to whether its appropriation could foster micropolitics, a situational politics based on local knowledge and action, in subaltern groups subjected to both the domination of the centre and the resulting capitalist social relations of production that stem from extended urbanisation. To devise the research strategies, four requirements were considered: to approach the object from different levels of analysis by using Lefebvres idea of social levels; to develop a specific tooling to address these levels by grounding the research in a Marxian based theoretical framework while using the Actor-Network theory as an empirical tool for the fieldwork; to investigate communities in both central and peripheral countries in the same scale of analysis by having case studies in Brazil (Santo Antônio do Salto and Noiva do Cordeiro) and in the UK (Pendeen); and to focus on the marginalised by using the lenses of an extended urbanisation. Noiva do Cordeiro is the main case study, while Santo Antônio do Salto and Pendeen are supporting cases. The results suggest that global relations of dependency and the top-down delivery of the internet contribute to the further peripheralisation of the rurban. Five assumptions stem from the work produced in this research. First, there is a conflictual relationship between rural and urban elements in rurban communities and these are enhanced with the introduction of the internet; second, the way the internet is introduced in the rurban has an impact on the way people appropriate it; third, still, even under marginalised conditions, there are indications that the introduction of the internet, when done in a bottom-up way, may lead to or enhance micropolitical actions; fourth, the collective appropriation of the internet has a direct relationship with existing socio-spatial practices, and it needs, therefore, a fostering space to occur; and fifth, despite the hopes of a liberating potential of the internet, its introduction in rurban communities tends to change socio-spatial relations in a heteronomous manner.